Orthorhombic CaFe2O4 microrod anode for lithium–ion battery. (21st August 2020) - Zhang, Kai; Hong, Weifeng; Gao, Ping; Ding, Rui; Liu, Enhui
Abstract: The orthorhombic CaFe2 O4 microrod has been facilely synthesized via a moderate precipitation–calcination process. Structural features and electrochemical performance of the CaFe2 O4 have been investigated. When used for lithium–ion battery, the moderate surface energy of CaFe2 O4 microrod is beneficial for preventing material agglomeration. CaFe2 O4 microrod displays the low-temperature lithium–ion storage ability such that even when tested at −20 °C its reversible specific capacity gets exceeded 100 mAh g −1 reversible specific capacity. Its room/high temperature electrochemical performance is also excellent. At the room temperature, the specific capacity contribution with 63–74%/96–98% of the first/third cycles are driven by surface controlled pseudocapacitance. Highlights: A moderate way to synthesize orthorhombic CaFe2 O4 microrod. The moderate surface energy of CaFe2 O4 is helpfully preventing agglomeration. Pseudocapacitance-driven orthorhombic CaFe2 O4 microrod anode. CaFe2 O4 microrod anode shows wide-range operating temperature of Li + storage ability.